Enhancement of Biosugar Production Via Enzymatic Yydrolysis of Sodium Hydroxide Pretreated Oil Palm Bagasse: A Statistical Perspective - Aina Fauzi, Nurul; Harun, Shuhaida; Md Jahim, Jamaliah; Ping Tan, Jian (International Journal of Engineering and Technology, 2019)
Oil palm frond bagasse (OPFB) is the major agriculture waste from the production of palm oil with 0.66g/g of total carbohydrate to serveas potential carbon source for downstream processing in producing succinic acid. This study focused in determining the optimum processvariable conditions for the 1% glucan loading for enzymatic hydrolysis process with commercial blending cellulase enzyme mixture ofCellic CTec 2 and hemicellulase enzyme of Cellic HTec 2. Using statistical approach of Response Surface Methodology, three independentprocess variables; specific enzyme activity (5 - 80 FPU/g glucan), hydrolysis temperature (30 - 70 °C), and agitation speed (100 - 180rpm) were investigated at five different levels (-α,-1, 0, +1, +α). The regression models indicated that R2 for glucan conversion at 1% GLenzymatic hydrolysis was 97.2% showing the experimental variations were well-defined by the models. For the lack of fit test, the pvalues> 0.05 proves that the model was significant to the prediction model. While both specific enzyme activity and hydrolysis temperaturewere statistically significant, there was no interaction observed between these variables. Although experimental runs reported themaximum glucan conversion of 94% was achieved in the 1% GL hydrolysis with 83.75 FPU/g glucan and 50C after 96 hours of saccharificationprocess, through validation process, the optimum conditions were determined at 30 FPU/g glucan, 45oC and 100 rpm respectivelywhere these saccharification conditions achieved 90% glucan conversion within 72 hours
Keywords: ANOVA; commercial enzyme; glucan conversion; oil palm frond; response surface methodology